Character Internalization Model in Online Learning: Model Internalisasi Karakter dalam Pembelajaran Online - Andriany, Fina; Imron, I; Mawardi, Imam (Prosiding University Research Colloquium, 2024)
Educationis the spear head of a country.Because a country will be said to be successfulif in the implementation of education has metthe existing educational standards in a country. During the Covid-19 pandemic, educational activities have changed. All elements of education are forced to carry out distance learning activities or online learning. Learning activities carrie dout at home have a positive and negative impact on teachers and students. Many problems are experienced during online learning activities. The decline in character education for students is felt once when students experience online learning.This happens because learning is carried out at home with minimal supervision from teachers, even parents at home who have more time to meet their children have not maximize dinsupervising the irchildren when learning online at home. This study took a qualitative descriptive approach. Data collection through interview studies, data collection throug observation and documentation studies. The results show edanincrease in thechar acter of students during online learning carried outusing the Zoom Meet platform, Whatsapp Group, Google meet and home visits to students'home inrotation according to the group schedule provided by the school. Religious characteris instilled by praying together before and after learning, the practice of dhuha prayers at home, supervision of dhuha prayers during home visits,and the cultivation of tolerance valuesin learning.Students Education is the spearhead of a country. Because a country will be said to be successful if in the implementation of education has met the existing educational standards in a country. During the Covid-19 pandemic, educational activities have changed. All elements of education are forced to carry out distance learning activities or online learning. Learning activities carried out at home have a positive and negative impact on teachers and students. Many problems are experienced during online learning activities. The decline in character education for students is felt once when students experience online learning. This happens because learning is carried out at home with minimal supervision from teachers, even parents at home who have more time to meet their children have not maximized in supervising their children when learning online at home. This study took a qualitative descriptive approach. Data collection through interview studies, data collection through observation and documentation studies. The results showed an increase in the character of students during online learning carried out using the Zoom Meet platform, Whatsapp Group, Google meet and home visits to students' homes in rotation according to the group schedule provided by the school. Religious character is instilled by praying together before and after learning, the practice of dhuha prayers at home, supervision of dhuha prayers during home visits, and the cultivation of tolerance values in learning. Students are given independent and group tasks to instill an independent attitude and mutual assistance. Teachers instill the importance of the nature of the Prophet such as shiddiq, tabligh, Amanah, and fathonah to instill the character of students. All teachers and parents collaborate and strengthen each other's roles in supporting the strengthening of character education values during students carrying out learning from home.